Publication Rate of Presentations at a National Physical Medicine and Rehabilitation Scientific Conference From 2009 to 2018. (February 2022) - Rhee, Jess; Bateman, Emma A.; Winston, Paul; Dow, Heather; Loh, Eldon; Viana, Ricardo
Abstract : Abstract: Conferences are important platforms for sharing research, but full-text publication is necessary for broader dissemination and impact. Few studies have examined the abstract-to-publication rate for physical medicine and rehabilitation. This study aimed to determine the abstract-to-publication rate of research abstracts presented from 2009–2018 at the Canadian Association of Physical Medicine and Rehabilitation annual scientific meetings. Using the official book of abstracts from 2009 to 2018, year of conference, abstract title, author names, and the affiliation/level of training of the first author were extracted. Systematic searches of abstract key words, authors' names, and the abstract title were performed using PubMed and Google Scholar to determine whether an abstract proceeded to full-text publication; if so, the date and journal of publication were extracted. Of the 524 total abstracts presented at the Canadian Association of Physical Medicine and Rehabilitation from 2009 to 2018, 187 went on to full-text publication for an abstract-to-publication rate of 35.8%. The mean time to full-text publication was 23.4 ± 8.63 mos. The abstract-to-publication rate was 18.6% for medical students, 28.7% for residents, 41.1% for physical medicine and rehabilitation consultants, and 49.4% for nonphysician presenters. This study highlights that low abstract-to-publication rates for novel research presented at the Canadian Association of Physical Medicine and Rehabilitation disproportionately affects trainees. Further research is needed to identify and remedy barriers to publication. Abstract : Supplemental digital content is available in the text.